2019
DOI: 10.3390/su11010231
|View full text |Cite
|
Sign up to set email alerts
|

Explicating Perceived Sustainability-Related Climate: A Situational Motivator of Pro-Environmental Behavior

Abstract: Individuals take cues from their surroundings when deciding whether to perform pro-environmental behaviors. Previous studies have acknowledged the role of structural, policy, and communication efforts to encourage pro-environmental behavior. Such studies demonstrate the importance of evaluating the external contexts when examining behaviors. Yet, there is a lack of explication of what external context is entailed. Expanding the concept of perceived sustainability-related climate (PSRC) used in organizational c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
26
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 40 publications
(29 citation statements)
references
References 64 publications
3
26
0
Order By: Relevance
“…Therefore, prior research asserts the need for integrating social and environmental issues in business strategy and operations (Aguinis and Glavas, 2012; Bansal and Hoffman, 2012; Testa et al, 2016, 2018). Past research has made invaluable contributions by foregrounding the role that formal mechanisms, such as environmental safety and health management systems, monitoring activities, and operational control, play in accentuating social responsibility and environmental sustainability (Darnall and Edwards, 2006; Darnall et al, 2008; Heras-Saizarbitoria and Boiral, 2013; Leung and Rosenthal, 2019; Peng and Lee, 2019).…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, prior research asserts the need for integrating social and environmental issues in business strategy and operations (Aguinis and Glavas, 2012; Bansal and Hoffman, 2012; Testa et al, 2016, 2018). Past research has made invaluable contributions by foregrounding the role that formal mechanisms, such as environmental safety and health management systems, monitoring activities, and operational control, play in accentuating social responsibility and environmental sustainability (Darnall and Edwards, 2006; Darnall et al, 2008; Heras-Saizarbitoria and Boiral, 2013; Leung and Rosenthal, 2019; Peng and Lee, 2019).…”
Section: Introductionmentioning
confidence: 99%
“…This was the thrust of hypotheses H7 to H11 and RQ1. Consistent with previous work (e.g., Massu et al, 2018;Leung & Rosenthal, 2019), the results suggest that perceived organisational support influences intention indirectly by changing how individuals think and feel about the behaviour, which then affects their intentions. Specifically, the results showed that perceived organisational support has a positive indirect effect on intention through injunctive norm and perceived behavioural control.…”
Section: Predicting Nurses' Intention and Use Of Smartphones For Worksupporting
confidence: 90%
“…There is a certain causal logic to that sequence, which is a requirement of mediation analyses (Hayes, 2013); though, the current results, being cross-sectional, cannot resolve any causal ordering among the variables of interest. Regardless, this finding extends Organisational Support Theory since very few studies demonstrate such result (e.g., Massu et al, 2018;Leung & Rosenthal, 2019) as compared to those that depict a direct relationship between organisational support and intention or acceptance to use organisational technologies (e.g., Hsiao & Chen, 2015;Park & Chen, 2007;Putzer & Park, 2010). A key takeaway from this result is that hospital policy (a reflection of organisational support enacted by hospital administrators and colleagues) can affect intention to use smartphones work purposes, but that influence is indirect.…”
Section: Predicting Nurses' Intention and Use Of Smartphones For Worksupporting
confidence: 55%
See 1 more Smart Citation
“…Although sustainable behaviour is, in practical terms, synonymous with "pro-environmental behaviour," the latter has been used to emphasize efforts to protect the natural environment, while the former specifies actions aimed at protecting both the natural and the human (social) environments. According to Leung and Rosenthal (2019), heightened attention to environmental issues has motivated scholars from across disciplines to understand why people engage in pro-environmental behaviours.…”
Section: Aspects Of Motivation For Sustainable Behaviourmentioning
confidence: 99%